Initial Reports of the Deep Sea Drilling Project 1986
DOI: 10.2973/dsdp.proc.87.112.1986
|View full text |Cite
|
Sign up to set email alerts
|

Turbidite Sedimentation in the Nankai Trough as Interpreted from Magnetic Fabric, Grain Size, and Detrital Modal Analyses

Abstract: At Site 582, DSDP Leg 87, turbidites ~ 560 m thick were recovered from the floor of the Nankai Trough. A turbidite bed is typically composed of three subdivisions: a lower graded sand unit, an upper massive silt unit, and an uppermost Chondrites burrowed silt unit. The turbidites intercalate with bluish gray hemipelagic mud which apparently accumulated below the calcite compensation depth. In order to investigate the nature and provenance of the turbidites, we studied the grain orientation, based on magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 6 publications
11
75
1
Order By: Relevance
“…The amount of detrital smectite derived from subaerial weathering of volcanic rocks is relatively small. Our provenance interpretations for the fine-grained sediments reinforce previous contentions of Taira and Niitsuma (1986), who suggested that the sand-sized sediment came largely from the Japan Alps, which had formed in the collision zone between the Izu-Bonin arc and the Honshu arc ( Fig. 1).…”
Section: Clay Mineralogy and Diagenesissupporting
confidence: 78%
“…The amount of detrital smectite derived from subaerial weathering of volcanic rocks is relatively small. Our provenance interpretations for the fine-grained sediments reinforce previous contentions of Taira and Niitsuma (1986), who suggested that the sand-sized sediment came largely from the Japan Alps, which had formed in the collision zone between the Izu-Bonin arc and the Honshu arc ( Fig. 1).…”
Section: Clay Mineralogy and Diagenesissupporting
confidence: 78%
“…The provenance must be from a polymictic province. The data agree well with Taira and Niitsuma's (1986) tabulation and support their inference on the Suruga Trough-Fuji River drainage source (Fig. 48, Sedimentary Petrology section, Site 808 chapter).…”
Section: Mineralogy and Diagenesissupporting
confidence: 75%
“…Early theoretical and laboratory studies indicate that AMS of studied rocks arises from the preferred orientation of elongate and flattened magnetic grains and could, therefore, be used as a measure of the degree and orientation of particle alignment, which in turn helps depicting palaeocurrent directions conditions [52] Hamilton and Rees 1970). Further comparative studies indicate that fabric and palaeocurrent estimated using AMS are in good agreement with those obtained from photometric, optical and other related methods [53][54][55].…”
Section: Magnetic Anisotropy and Rock Propertiessupporting
confidence: 58%